KONSEPSI RESTORATIVE JUSTICE SEBAGAI UPAYA PENYELESAIAN TINDAK PIDANA LALU LINTAS POLRES MAJENE - Sauqi, Muh. Ikbal; Dj, Akhdiari Harpa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The problems studied in this paper are about how to apply the concept of restorative justice in the case of traffic accidents in the majene police jurisdiction and how to account for the concept of restorative justice in the case of traffic accidents in the jurisdiction of the Majene Police The method used in the writing of this ilimiah work is a joint research method is a procedure for data collection, Data analysis, by sequential use of quantitative and qualitative methods or vice versa, in gaining a deeper understanding of the main problem. through normatuf legal research approaches and empirical legal research. The purpose of this study is to find out and understand how the concept of Restorative justice is implemented in the case of traffic accidents in Majene Police and how criminal accountability in traffic accident cases. Based on the results of the research, it can be concluded that the Concept of Restorative Justice is expected to be an alternative step for the political policy of legislation to solve problems in criminal law. Because, the policy of legislation that in principle is a policy to determine the direction and strengthen the politics of national law. Thus, the policy of such legislation must reflect the legal values that develop in society. With the implementation of Restorative Justice there are several foundations of thinking as mentioned above, the criminal justice system and prosecution are expected to provide the right direction in order to provide justice for the community with the aim of creating community welfare